The fashionable knowledge of management consulting - Lopes da Costa, R.; Miguel, I.; Tavares, F.; Barreiros, L. (Journal of Management and Sustainability, 2013)
In the evolution of strategic disciplines much of the knowledge produced has been widely diffused by the management consulting industry. But can this sector be regarded as knowledge intensive activity based on true structure of expertise knowledge? One way to understand if we can consider that sector as a source of knowledge dissemination is realizing its relationship with the market in terms of knowledge, rather than identify only as a set of static techniques to be applied as in most of times they have been doing. This article presents itself as a reflection about the real reasons for the increasing use ofmanagement consulting services, indicating simultaneously that can really be a true field of opportunities for the academic class if the study will focused in the establishment and institutionalization of micropractices (strategy-as-practice) that there are used and its implications in terms of organizational results.